2021
DOI: 10.1126/scitranslmed.abc3196
|View full text |Cite
|
Sign up to set email alerts
|

A subset of cytotoxic effector memory T cells enhances CAR T cell efficacy in a model of pancreatic ductal adenocarcinoma

Abstract: In humans, the natural killer (NK) cell marker CD161 identifies several subsets of T cells, including a polyclonal CD8 αβ T cell receptor–expressing subset with characteristic specificity for tissue-localized viruses. This subset also displays enhanced cytotoxic and memory phenotypes. Here, we characterized this unique T cell subset and determined its potential suitability for use in chimeric antigen receptor (CAR) T cell therapy. In mice, gene expression profiling among the CD161-equivalent CD8+ T cell popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…73 The prevailing memory phenotype and absence of a typical T cell exhaustion profile correlated with the antitumor effects and sustained and complete tumor remission in the xenograft model. 60,74,75 Reduction of TCR alloreactivity in CAR/TCR KO T cells observed in our study exhibited its therapeutic potentials to minimize the risk of GvHD in mice, which was demonstrated in previous studies. 22,60 To our knowledge, this study is the first to demonstrate that the combination of SB transposons and CRISPR-Cas9 enables efficient manufacturing of allogeneic TCR-disrupted CD19-CAR T cells, underscoring its novelty.…”
Section: Discussionsupporting
confidence: 80%
“…73 The prevailing memory phenotype and absence of a typical T cell exhaustion profile correlated with the antitumor effects and sustained and complete tumor remission in the xenograft model. 60,74,75 Reduction of TCR alloreactivity in CAR/TCR KO T cells observed in our study exhibited its therapeutic potentials to minimize the risk of GvHD in mice, which was demonstrated in previous studies. 22,60 To our knowledge, this study is the first to demonstrate that the combination of SB transposons and CRISPR-Cas9 enables efficient manufacturing of allogeneic TCR-disrupted CD19-CAR T cells, underscoring its novelty.…”
Section: Discussionsupporting
confidence: 80%
“…In addition to the increased expression of MHC genes and integrins, the Cytotoxic and Memory clusters also transcribed several receptors more typical of NK cells, including KLRB1 , which encodes CD161. CD161 is expressed by a subset of T cells with characteristic tissue homing( 61 ) and increased cytotoxicity ( 62 ), and recent work has shown that CD8+CD161+ T cells define a potent effector memory subset with enhanced CAR T cell efficacy ( 63 ). To explore this further, we turned to a recent study which identified a continuous gene expression gradient of lymphocyte innateness from T cells to NK cells( 64 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was speculated that switchable HER2-redirected CAR T cells are as effective as conventional HER2-redirected CAR T cells in vivo [ 121 ]. Another report has shown that HER2-specific CD8+CD161+ CAR T cells could eradicate HER2-expressing PDAC cells faster and with greater efficiency than HER2-specific CD8+CD161− CAR T cells [ 122 ]. Further, CD8+CD161+ CAR T cells could stimulate in vivo antitumor efficacy in xenograft models of HER2-expressing PDCA cells, with raised expression of granzymes and abridged expression of exhaustion markers [ 122 ].…”
Section: Her2-specific Cars In Human Tumor Therapymentioning
confidence: 99%
“…Another report has shown that HER2-specific CD8+CD161+ CAR T cells could eradicate HER2-expressing PDAC cells faster and with greater efficiency than HER2-specific CD8+CD161− CAR T cells [ 122 ]. Further, CD8+CD161+ CAR T cells could stimulate in vivo antitumor efficacy in xenograft models of HER2-expressing PDCA cells, with raised expression of granzymes and abridged expression of exhaustion markers [ 122 ]. Besides, Thakur et al [ 123 ] employed anti-CD19 CART armed with anti-CD3 (OKT3) × anti-HER2 bispecific antibodies (HER2Bi) or anti-CD3 (OKT3) × anti-EGFR bispecific antibodies (EGFRBi) to address the cytotoxicity against HER2 or EGFR positive cancer cell lines.…”
Section: Her2-specific Cars In Human Tumor Therapymentioning
confidence: 99%